2021
DOI: 10.1080/23311916.2021.1981519
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitory traffic signs violation by well-educated young drivers based on situation scenarios

Abstract: Traffic violations in Indonesia were mostly committed by young drivers. Surprisingly, university students ranked third as traffic violators despite they are expected to have better understanding of traffic signs instead of others. This study was conducted to investigate the influence factors that might encourage university students as well-educated young drivers to commit traffic violations through several situation scenarios. Five prohibitory traffic signs (no u-turn, no parking, stop sign, maximum speed limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…For instance, the drivers stating they do not like to wait at rail crossings, were associated with lower knowledge categories. Again, the findings are intuitive and supported by past research that reported drivers' impatience at traffic signals (41). Although driver behavior at traffic signals is a distinct field of research, it can nevertheless be compared with stop signs at rail crossings since it aids in comprehending drivers' patient or impulsive attitudes toward signs, warning devices, and signals.…”
Section: Resultssupporting
confidence: 75%
“…For instance, the drivers stating they do not like to wait at rail crossings, were associated with lower knowledge categories. Again, the findings are intuitive and supported by past research that reported drivers' impatience at traffic signals (41). Although driver behavior at traffic signals is a distinct field of research, it can nevertheless be compared with stop signs at rail crossings since it aids in comprehending drivers' patient or impulsive attitudes toward signs, warning devices, and signals.…”
Section: Resultssupporting
confidence: 75%